Potencial inibitório in vitro de biflavonoides de Garcinia gardneriana : um estudo sobre monoamina oxidades e CYP19 (aromatase) - Recalde Gil, Maria Angélica (2015)
The plant Garcinia gardneriana (Planch. & Triana) Zappi, popularly known in Brazil as "bacupari" has traditionally been used for various types of inflammatory diseases and the evaluation of their chemical composition, mainly of leaves, has resulted in biflavonoids as major compounds. These phenolic compounds have shown anti-inflammatory activity validating the popular use of the plant. In this work was isolated from dried branches of Garcinia gardneriana the biflavonoids: morelloflavone, that is an naringenin covalently linked to luteolin, Gb-2a which is an naringenin linked to eriodictyol and Gb-2a- 7-O-glucose. These compounds have been previously evaluated in various activities such as anti-inflammatory and anti-antioxidants but there is no report of its activity as enzymatic inhibitors. However, the monomers that form it, have been evaluated in the inhibition of aromatase and antidepressant activity with positive outcome, which commonly are used MAO-A inhibitors. In the isolation process were also founded terpenoid compounds as lupeol and friedelin The isolated and purified biflavonoids were used to evaluate enzyme inhibition "in vitro" in monoamine oxidases (MAO-A MAO-B) and aromatase. The compounds showed a positive response even of IC50 5,47 μM and 1,35 μM for MAO-A inhibition of and aromatase enzyme respectively; discovering a way for a new proposal to link both enzymes for treatment of hormone-dependent cancers and anxiety and depression disorders.